CONSUMER PREFERENCES IN CHOOSING MIDDLE CLASS HOUSING IN TANGERANG - Yosephine Sitanggang (Lakar: Jurnal Arsitektur, 2023)
Population growth and the development of economic activities in big cities have increased housing needs. This demand increase can be seen in the phenomena of the growing property market in Indonesia, such as housing. Along with the times, housing or residential does not only have a function to fulfill one of the main human needs, which is housing (residential), but also as an investment or asset. This has resulted a preference of consumers who also act as residents of the property to determine the housing that will be occupied and or owned. This research was carried out to identify the factors that influence housing preferences especially landed house property products for the middle class in Tangerang. This research is expected to be an input or reference for the design and implementation of sustainable architecture. This research used a descriptive analysis method with a qualitative approach. The data collection method was used to distribute the questionnaires through Google form by using purposive sampling technique to one of the family members from the middle class who lives in a landed house in Tangerang. This research has drawn preliminary conclusions about housing preferences of the middle class in Tangerang. Several factors that are preferred by the middle class in Tangerang are the price, the quality of the neighborhood, the building size, the developer, and the flood-free location.